Developing Reading Material based Think Pair Share Model to Enhance Students' Reading Skill on Fourth Semester English Students Prof. DR. Hazairin, SH University. - Elva utami Utami; Yosi marita Marita (English Education Study Program Faculty of Teacher Training and Education, 2018)
This study aimed to produce Reading Teaching Materials which valid and effective. It can use to the students especially for Reading subjects. Research and development design was used for this study. The research was conducted at Fourth Semester English Students Prof. DR. Hazairin, SH University. Data collecting techniques used were tests, interviews, and questionnaires. The Data were analyzed using descriptive analysis of quantitative and qualitative. The results showed that the materials developed are valid, and effective. The validity showed from the assessment of lesson plan (RPS), student worksheet (LKS), teaching materials, and tests of learning outcomes. While the effectiveness of reading teaching materials based on Think Pair Share model that have been developed by learning activity indicated enthusiastic students in the learning process by using Think Pair Share model achievements approval â‰¥ 75%. In addition to the learning outcomes of students have reached 92,5%. While the response of students to the learning process that had been conducted shows that the high positive response, the above achievements calculating response was 80%. Based on the results of data analysis, it can be concluded that the Reading teaching materials based Think Pair Share Model can be used and implemented on students, especially in the subject of Reading. Keywords : reading material, think pair share, reading skills.